(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
In this essay we discuss the image portrayed of Patagonia –in this case, that area which corresponds to Aysén– that is projected by the novel La Patagonia ya nunca sería la misma from the perspective and behavior of its protagonists. We study specifically the topic of pristine nature, which exerts a type of purifying effect on the conduct, attitude, and even spirituality, of the subjects that, at some point in their lives, have been instruments of “progress” and of industry in detriment of nature itself, as what transpires with the engineer named Letelier, a male protagonist of the novel. This occurs in the context of a battle against the eventual installment of a mega hydroelectric dam, known as HidroAysén, amongst the great rivers of the northern Patagonia.